Is an Alternative Globalization Possible? - Evans, Peter (Politics & Society, 2008)
Building on Polanyi's concept of the “double-movement” through which society defends itself against domination by the self-regulating market, this article sets out some key organizational and ideological hurdles that the contemporary “movement of movements” must surmount to challenge the hegemony of neo-liberal globalization. After outlining neo-liberalism's failures, it makes an argument for the possibility of “counter-hegemonic globalization,” defined as a globally organized project of transformation aimed at replacing the dominant (hegemonic) global regime with one that maximizes democratic political control and makes the equitable development of human capabilities and environmental stewardship its priorities.
Sociology
Keywords: double movement; globalization; neoliberalism; social movements; transnational networks

Pursuing a Great Transformation - Evans, Peter (Sociology of Development, 2015)
Polanyi offers a powerful vision of a “great transformation” that will reverse the subordination of society to the economy and reassert the primacy of social protection in the context of modern society. Pursuit of the great transformation is one way of conceptualizing the quest for “development” in the positive sense of ecologically sustainable human flourishing. This paper explores how the contemporary interaction of national and global political dynamics affects the trajectory of Polanyi's “double movement.” Does the shift of economic power to globally organized capital while the space for contentious politics remains primarily at the national level “checkmate” the movement for social protection? Or is there more potential for political contestation and policies supporting social protection at the national level than the “global checkmate” thesis claims? And, if so, can this potential be magnified by productive, synergistic alliances between national and global movements, resulting in a global auxiliary effect instead of a global checkmate effect? Answering these questions requires analyzing the relative autonomy of national political regimes vis-à-vis global capital as well as evaluating the ability of movements to connect effectively across levels.
Sociology
Keywords: Great Transformation; The (Book); double movement; global capital; social protection; transnational social movements

Polanyi meets Bolsonaro: Reactionary politics and the double movement in twenty-first-century Brazil - Evans, Peter (International Sociology, 2020)
Twenty-first-century Brazil’s political evolution is a window on the dynamics of contemporary political transitions. The inability of Brazil’s Workers’ Party to sustain its social democratic project and the subsequent rise of the reactionary regime of Jair Bolsonaro are, in turn, part of a global pattern of political change. Karl Polanyi’s vision of the ‘double movement,’ in which the dominance of the market vies with the countervailing movement for social protection, offers an analytical springboard for reflecting on these political transitions. Trying to understand the movement for social protection leads to examining ebbs and flows in the momentum of mobilization. Trying to understand how market dominance leads to reaction brings us back to Polanyi’s advocacy of ‘crass materialism’ as a lens for looking at reaction, and from there to consideration of how the structural power of capital undercuts efforts at social protection and opens the door to reaction.
Publisher: SAGE Publications Ltd
Keywords: Brasil; Brazil; Brésil; Polanyi; finance; finanzas; protección social; protection sociale; reacción; reaction; réaction; social protection